Effect of Omega-3 Supplementation on Major Adverse Cardiovascular Events (MACE): A Systematic Review - Aisy, Annesyia; Martineta, Meriza; Sari, Dina Keumala; Sitorus, Esther Reny Deswani (Buletin Farmatera, 2022)
Abstract: Major adverse cardiovascular events (MACE) are the most relevant outcome in cardiovascular secondary prevention because they are the main cause of mortality and morbidity in patients with cardiovascular disease. Due to the contrasting results between studies, omega-3 supplementation is believed to have cardioprotective effects, but its significance in reducing MACE is still in question. This study aims to determine the effect of omega-3 supplementation on the prevention of MACE. A literature search was carried out on several databases from September 820, 2021. Selection of literature is done through the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flowchart. Literature that is eligible was then assessed qualitatively. We compared the hazard ratio of each key outcome of interest, which was included in the primary and secondary end-point of each study. Among 2049 publications found from the initial literature search, 6 publications were included in this study. The analysis showed a significant reduction in cardiovascular risk in participants with a high dose of pure EPA. Studies with a lower dose of omega-3 that contains a combination of EPA and DHA did not provide similar significant results. The use of high-dose omega-3 supplementation with pure EPA content can significantly reduce